Curating computer heritage: A case study - Stachniak, Zbigniew (Scientia Canadensis, 2024)
Preserving legacy computer systems poses a complex challenge, given the inherent intricacies of these devices. While numerous organizations dedicated to safeguarding computing heritage have identified key challenges and produced reports and general guidelines for best preservation practices, the vast array of object categories, types, and numerous other factors may render such studies inadequate for the preservation task at hand. This paper is focused on specific challenges in the preservation of historical computer systems, using the MCM/70 preservation project conducted at the York University Computer Museum as a case study.